Assessing the Threat Posed by Registered Firearms Dealers in the UK. (23rd May 2019) - Bryant, Robin; Arditti, Roger; Gustafson, Kristian
Abstract: This article examines the threat posed by Registered Firearms Dealers (RFDs) in the UK, based on an analysis of 12 case studies of dealers found to have committed serious criminal acts and 29 semi-structured interviews with law enforcement agencies and representatives of 'shooting' organizations. The analysis reveals a number of concerns with the regulatory and enforcement regimes surrounding RFDs. Our research demonstrates that RFDs have the capability and opportunity to pose a threat to public security but a key challenge remains to identify and assess the likelihood of RFD criminal intent. At the time of writing, there were no standardized structured methodologies to identify intent during the RFD licencing process. However, via a novel 'Indicators and Warnings' analysis, we provide a basis for how this might be undertaken. The article concludes with a discussion about how the potential threat posed by a small minority of RFDs might be reduced.